Investigating the potential role of DNA (hydroxy)methylation in the control of post-stroke axon growth - Wallis, Marcus (2020)
An important mechanistic factor of functional recovery following ischemic stroke is the sprouting of new axons and repair of damaged axons in the region around the infarct. To induce this axonal growth, regulation of gene expression is required. Whilst some previous research has characterised a role of DNA methylation (5-methylcytosine, 5mC) in this regulation, less is known about what role, if any, oxidised forms of 5mC perform. 5mC is oxidised by Tet enzymes to form 5-hydroxymethylcytosine (5hmC), which acts mainly as an intermediate of demethylation and is therefore associated with increased gene expression. It has been previously shown that global 5hmC levels increase following ischemic stroke, although no determination has been made as to how this increase influences post-stroke axon growth.